Metodologia Híbrida para a Previsão dos Preços do Mercado Elétrico com Integração Renovável - Vasco Miguel Agante Campos (2018)
Due to the new paradigm for an intelligent, decarbonized and sustainable electric sector, the challenges to profitability and correct management are still considerable. However, with tools and techniques that allow a real, robust and cost-effective approximation by way of forecasting, it is possible to minimize costs, flexibilize and improve the overall operability of the system. Thus, the objectives are: 1. Bibliographic review of the most recent forecasting methodologies proposed in the scientific community. 2. Development of a methodology for forecasting renewable energy profiles (wind and photovoltaic) and electricity price profiles in the short time interval, considering, for example, hybrid forecasting techniques.